2019
DOI: 10.1080/21645515.2018.1556076
|View full text |Cite
|
Sign up to set email alerts
|

A campaign aimed at increasing seasonal influenza vaccination coverage among post graduate medical residents in an Italian teaching hospital

Abstract: We analysed the impact of several strategies aimed at increasing influenza immunisation rates among Medical Residents (MRs) of an Italian teaching Hospital.During the 2015-16 and 2016-17 influenza seasons we carried out several interventions: ambulatory doubling where vaccination was offered, ambulatory opening hour extension, email invitations, informative materials, forum theatre and vaccination campaign conference. In addition, during the 2016-17 the OSV was carried out: MRs who go to specific wards where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
(19 reference statements)
2
15
0
Order By: Relevance
“…The age distribution of vaccinated HCWs during the last four seasons suggested, especially among young HCWs, a satisfactory effectiveness of informative and communicative campaigns based mainly on social networks and new social media, as previously reported in other experiences [20][21][22]. In particular, the significant decrease of the mean age of HCWs vaccinated confirmed a better response to strategies promoted at the UH of Palermo among health-care professionals under 40 years old.…”
Section: Discussionsupporting
confidence: 75%
“…The age distribution of vaccinated HCWs during the last four seasons suggested, especially among young HCWs, a satisfactory effectiveness of informative and communicative campaigns based mainly on social networks and new social media, as previously reported in other experiences [20][21][22]. In particular, the significant decrease of the mean age of HCWs vaccinated confirmed a better response to strategies promoted at the UH of Palermo among health-care professionals under 40 years old.…”
Section: Discussionsupporting
confidence: 75%
“…Organizational aspects which facilitated access to the vaccine were implemented in eight studies [18,[21][22][23][24][25][26][27]; however, OSV was highlighted as a main intervention in only four campaigns [23,[25][26][27]. OSV as implemented key intervention increased VC overall by 113.6% (SD: ± 102.7%, range 30.8%-263.6%) (Table1).…”
Section: Key Intervention: Organizational Strategiesmentioning
confidence: 99%
“…Similar evidence has been gathered in an Italian setting [ 13 , 14 , 15 , 16 ]. However, recent shreds of evidence relating to the Italian context have shown that specific organizational and educational interventions may have mixed results in ameliorating influenza VC [ 17 , 18 , 19 , 20 ]. Thus, research is important in finding variables useful in designing systematic interventions aimed at implementing HCWs vaccination coverage.…”
Section: Introductionmentioning
confidence: 99%